Developmental Potential and Efficiency of Black Bengal Goat Embryo Production by using Intracytoplasmic Sperm Injection and In Vitro Fertilization - Bori, Joygeswar; Boruah, Jyoti Lakshmi Hati; Phukan, Amlan Jyoti; Chandra Sarkhel, Bikash; Kumar, Dharmendra; Morang, Munmi (The Indian Journal of Animal Reproduction, 2025)
This study aimed to optimize an intracytoplasmic sperm injection (ICSI) for in vitro embryo production in black bengal goats and compare its efficiency with in vitro fertilization (IVF). A total of 744 oocytes were retrieved from 269 slaughter house-derived ovaries, with an average recovery rate of 2.76 oocytes per ovary. Only grade I and II oocytes (n = 534) were selected for maturation, of which 376 (70.41%) reached metaphase II. For ICSI, epididymal sperm with broken tails were microinjected into mature oocytes using a 5 µm micropipette, yielding a high survival rate (83.21%) and a low degener ation rate (17.78%, p < 0.05). Chemical activation using ionomycin, cycloheximide (CHX), and 6-DMAP resulted in a 74.44% cleavage rate (p<0.05). Developmental rates in the ICSI group (n = 90) were: 74.44% (2-cell), 63.33% (4-8 cell), 44.44% (8-16 cell), 23.33% (morula), and 14.44% (blastocyst). A comparative analysis revealed that ICSI resulted in higher early cleavage rates (73.40 ± 3.12%) compared to IVF (64.06 ± 2.44%). In contrast, IVF produced a greater pro portion of morulae (37.90 ± 3.15%), while ICSI resulted in 23.20 ± 2.73%. Similarly, blastocyst formation was higher in the IVF group (21.05 ± 2.09%) than in the ICSI group (14.56 ± 1.75%). These findings suggest that ICSI is equally effec tive as IVF in generating competent embryos. With ICSI achieving higher early cleavage rates and IVF supporting better development at later stages. ICSI can therefore be considered a practical alternative to IVF for goat embryo production; however, it requires further study with larger cohort. Additionally, the study demonstrates that using a fine 5 µm micro pipette for ICSI, offers a precise, efficient, and cost-effective technique, especially well-suited for utilizing oocytes from slaughterhouse sources and sperm retrieved from the epididymis.